Hierarchy, strategic assets and distinctive capabilities in Scottish organised crime - Murray, Kenneth (Constructing and organising crime in Europe / Petrus C. van Duyne, Alexey Serdyuk, Georgios A. Antonopoulos, Jackie H. Harvey, Klaus von Lampe (Eds.); Kharkiv National University of Internal Affairs, Northumbria University, Teesside University, Utrecht University. – Chicago-Kharkiv : Eleven International Publishing, Kharkiv National University of Internal Affairs, 2019. - P. 205-23, 2019)
У цьому розділі розглядається значення ієрархії в шотландської організованої злочинності: докази, що підтверджують її існування, і умови, необхідні для її виникнення. При цьому в розділі розглядається, як групи організованої злочинності в Шотландії конкурують на своїх основних ринках, як кримінальних, так і законних, з акцентом на ринкові фактори і динаміку, необхідні для виживання, витривалості і домінування. Виходячи з цього, пропонується платформа для аналізу, яка покликана допомогти виявити відмінні можливості домінуючих груп організованої злочинності і то, як вони дозволили розвитку стратегічних активів сформувати основу їх ієрархічної сили.

This chapter considers the significance of hierarchy in Scottish organised crime: the evidence that supports its existence and the conditions that are necessary for its occurrence. In doing so the chapter examines how Serious Organised Crime Groups (‘SOCGs’) in Scotland compete in their principal markets, both criminal and legitimate, focussing on the market factors and dynamics that are necessary for survival, endurance and dominance. On this basis, a platform for analysis is proposed which is designed to assist in identifying the distinctive capabilities of dominant SOCGs and how these have enabled the development of the strategic assets form the basis of their hierarchical strength. A practical application of this approach is proposed to enable SOCG vulnerabilities to be identified such that their activities and influence, not least in legitimate markets, can be curtailed, or at least more effectively constrained.

В этой главе рассматривается значение иерархии в шотландской организованной преступности: доказательства, подтверждающие ее существование, и условия, необходимые для ее возникновения. При этом в главе рассматривается, как группы организованной преступности в Шотландии конкурируют на своих основных рынках, как криминальных, так и законных, с акцентом на рыночные факторы и динамику, необходимые для выживания, выносливости и доминирования. Исходя из этого, предлагается платформа для анализа, которая призвана помочь выявить отличительные возможности доминирующих групп организованной преступности и то, как они позволили развитию стратегических активов сформировать основу их иерархической силы.
Murray, K. Hierarchy, strategic assets and distinctive capabilities in Scottish organised crime / Kenneth Murray // Constructing and organising crime in Europe / Petrus C. van Duyne, Alexey Serdyuk, Georgios A. Antonopoulos, Jackie H. Harvey, Klaus von Lampe (Eds.); Kharkiv National University of Internal Affairs, Northumbria University, Teesside University, Utrecht University. – Chicago-Kharkiv : Eleven International Publishing, Kharkiv National University of Internal Affairs, 2019. - P. 205-233. - DOI: https://doi.org/10.32631/ccc19.09.
Keywords: Constructing and organising crime in Europe; Materials of conferences. Збірники матеріалів наукових конференцій. Сборники материалов научных конференций; Кримінологія. Criminology. Криминология; Наукові публікації. Scientific publications. Научные публикации; organised crime; Scotland; Шотландия; Шотландія; організована злочинність; организованная преступность; зарубежный опыт; зарубіжний досвід; foreign experience